2011
DOI: 10.1038/leu.2011.256
|View full text |Cite
|
Sign up to set email alerts
|

Impaired bortezomib binding to mutant β5 subunit of the proteasome is the underlying basis for bortezomib resistance in leukemia cells

Abstract: Proteasome inhibition is a novel treatment for several hematological malignancies. However, resistance to the proteasome inhibitor bortezomib (BTZ, Velcade) is an emerging clinical impediment. Mutations in the b5 subunit of the proteasome, the primary target of BTZ, have been associated with drug resistance. However, the exact mechanism by which these mutations contribute to BTZ resistance, is still largely unknown. Toward this end, we here developed BTZ-resistant multiple myeloma (8226) and acute lymphoblasti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
206
2
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(221 citation statements)
references
References 48 publications
11
206
2
2
Order By: Relevance
“…Mutations on the b5 subunit (PSMB5) of the 20S proteasome have been associated with bortezomib resistance since it reversibly inhibits the chymotrysinlike activity of the b5 subunit of the proteasome. 28,29 As shown in Supporting Information Fig. S5, KMS20 and KMS28BM cells have possessed identical genomic DNA sequence of PSMB5 without mutation.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations on the b5 subunit (PSMB5) of the 20S proteasome have been associated with bortezomib resistance since it reversibly inhibits the chymotrysinlike activity of the b5 subunit of the proteasome. 28,29 As shown in Supporting Information Fig. S5, KMS20 and KMS28BM cells have possessed identical genomic DNA sequence of PSMB5 without mutation.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro biochemical experiments, however, revealed that introduction of the A49V point mutation did not recapitulate the full salinosporamide A resistance phenotype as the original SalI subunit (Kale et al, 2011). Since hematologic tumor cell lines with in vitro acquired resistance to bortezomib have also displayed similar mutations in exon 2 of PSMB5 (Oerlemans et al, 2008;Ruckrich et al, 2009;Ri et al, 2010;Balsas et al, 2012;de Wilt et al, 2012;Franke et al, 2012;Verbrugge et al, 2012), this points to a common mechanism of resistance to proteasome inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…While BTZ‐adapted haematological cell line models frequently acquire mutations in β5 that confer resistance to BTZ, these mutations are absent in clinical specimens obtained from BTZ‐resistant patients (reviewed in Niewerth et al , 2015). Several studies indicate that overexpression of catalytic subunits is the primary cellular response mechanism to BTZ treatment and may precede acquisition of β5 mutations (Franke et al , 2012; Niewerth et al , 2013), as well as increased β2 and β1 activity (Ruckrich et al , 2009). Given that both pan‐proteasome inhibitory activity (Britton et al , 2009) and irreversible binding to the proteasome subunits (Orlowski, 2013; Dou & Zonder, 2014) have been postulated to overcome BTZ resistance and provide prolonged activity, the unique pharmacological profile of MRZ may confer therapeutic advantage by irreversibly inhibiting more than one proteasomal activity (reviewed in Kale & Moore, 2012).…”
mentioning
confidence: 99%